The relationship among the digit ratio (2D:4D), physical activity, aggression and sensation seeking in mature and immature boys - Taher Afsharnezhad; Farahnaz Ayatizadeh Tafti; Ali asghar Marzi; Nazanin Maleksabet (Sport Sciences and Health Research)
Background: Digit ratio (2D:4D) is a marker of prenatal androgen exposure that has been associated with behavioral parameters. Individuals with low 2D:4D are more aggressive and tend to engage in more physical activity.Aim: We examined the relationship between 2D:4D and physical activity, sensation seeking and aggression in mature and immature boys.Materials and Methods: The study population consisted of Mazandaran male students aged 9 to 17 years in 2019-2020. The sample was 218 healthy, cluster randomly selected boys (13.77±2.4 y/o) from three schools with no health issues. 2D:4D digit ratio, physical activity, aggression, sensation seeking were measured. Pearson correlation analyzed variable associations. Significance was considered at P≤0.05.Results: Low 2D:4D ratio was associated with higher physical activity (r≈-0.27), sensation seeking (r≈-0.3), and aggression (r≈-0.21), during childhood and adolescence (P<0.05). These relationships among right and left hand 2D:4D ratios with physical activity and sensation seeking remained consistent across maturity levels (P<0.05). Only immature boys had a significant association between 2D:4D ratios and aggression (r≈-0.29, P<0.05). Physical activity was positively associated with sensation seeking (r≈0.25, P<0.05), but not aggression in mature and immature boys.Conclusion: Prenatal testosterone organizes boys' physical activity and behavioral parameters, influencing the later development of sensation-seeking and aggression and greater participation in physical activity. The study has limitations such as a small sample size and a self-report method for assessing aggression. Future research should focus on behavioral observation methods with larger sample sizes.